Encroachment on the health of a person for the purpose of intimidation: the concept, content and criminally-legal value - Катеринчук, Катерина Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is dedicated to problems of terminology and definitions intimidation as the concept. Analyzed the terms contained in the criminal law is a "psychological violence", "threat," " intimidation," "coercion." Some aggravating circumstances of the crimes against the person health providing one of the features as the intimidation. However, these articles have certain characteristics, such as: intended grievous bodily injury (ch. 2, Art. 121 CC) with a special purpose - to intimidation the victim or other persons; intentional moderate bodily injury (ch. 2, Art. 122 CC) - intimidating the victim or his family or coercion to certain actions; beatings and torture (ch. 2, Art. 126 CC) - intimidating the victim or his relatives. Such differences aggravating circumstances of the crimes against the person’s health in practice can be a prerequisite confusion and irreparable mistakes. In addition, the theory of criminal law contains identical (similar) terms that are substantially the same. Therefore, it causes debate among scientists from various areas of knowledge (law and psychology). However, specifics determine the content of "intimidation" and its comparison with other criminal-legal categories, led the development of this research to improving current legislation of Ukraine and the practice of criminal law, such as crimes against the health of individuals in the purpose of intimidating. We did the analyses of the scientists’ works according to subject of this article and as the result we offered own vision for improving the law on criminal liability offenses against a person’s health. So, violence is possible, in the physical and mental ways. "Intimidation" and "threat" is synonymous and is part of "psychological violence". Analysis of the term "compulsion" makes it possible to argue that this concept is not identified with "Intimidation", "threat" and is also part of "psychological violence". It could lead to conflict and impacts on the formula for qualification in the articles of crimes against the person’s health were could be used intimidation in the causes of it discrepancy. For example, skilled crimes against a person’s health - is intimidation not only the victim but also other persons (ch. 2, Art. 121 of the Criminal Code), or relatives (ch. 2, Art. 122 of the Criminal Code) and his family (p. 2, Art. 126 CC). Therefore, we believe it is appropriate to establish a "full" circle of persons defined in each article of the Criminal Code or the total complement of an article as an example of the Criminal Procedure Code of Ukraine, which will be hosted definition of terms contained in the Criminal Code.